Biosignal Processing - Asadpour, Vahid; Karakuş, Selcan (Biomedical Engineering, 2022)
Biosignal processing is an important tool in medicine. As such, this book presents a comprehensive overview of novel methods in biosignal theory, biosignal processing algorithms and applications, and biosignal sensors. Chapters examine biosignal processing for glucose detection, tissue engineering, electrocardiogram processing, soft tissue tomography, and much more. The book also discusses applications of artificial intelligence and machine learning for biosignal processing.